Age related changes in the primary somatosensory area of the cerebral cortex - Joseph, Santos George; George, Anne (Asian Journal of Medical Sciences, 2020)
Background: Age-related changes in structural and functional part of brain have been the motivation of previous and ongoing neuroscientific research. The focus of most studies done, were on different motor areas of the of the cerebral cortex. Very few studies were done on primary somatosensory areas of the brain. Aims and Objective: The aim of the study was to investigate the age-related changes in primary somatosensory area of the cerebral cortex of the human brain. Materials and Methods: The study was conducted on 50 autopsied brain specimens. The specimens removed were of both sexes belonging to various age groups ranging from 9 months to 75 years. The specimens were collected from the Department of Forensic Medicine, Medical College Kottayam. During the autopsy the meninges were carefully stripped off. The sulci and gyri were then examined carefully. Results: The depth of the upper area of the central sulcus is more than the middle and lower areas, both in the right and left halves of the cerebral cortex. The laminae of the primary somatosensory area have shown that as age advances there is a progressive increase in thickness except in the case of lamina IV. From the ages of 61 years onwards, laminar degeneration takes place. The thickest lamina was lamina V. The thinnest lamina was lamina IV. The stellate cells that dominate in lamina II and IV show a difference in their arrangement. In foetal life, the pyramidal cells were almost indistinguishable from the stellate cells. The pyramidal cells were seen mostly in lamina III and V. Conclusion: The study results suggest the possibility that in the more advanced stages of aging, the structural integrity of lamina IV is more consistent than other layers present in primary somatosensory area of the cerebral cortex. Further study is needed to examine the impact of ageing on somatosensory area.